2015
DOI: 10.1177/1559325815611904
|View full text |Cite
|
Sign up to set email alerts
|

Biological Response of Positron Emission Tomography Scan Exposure and Adaptive Response in Humans

Abstract: The biological effects of exposure to radioactive fluorodeoxyglucose (18F-FDG) were investigated in the lymphocytes of patients undergoing positron emission tomography (PET) procedures. Low-dose, radiation-induced cellular responses were measured using 3 different end points: (1) apoptosis; (2) chromosome aberrations; and (3) γH2AX foci formation. The results showed no significant change in lymphocyte apoptosis, or chromosome aberrations, as a result of in vivo 18F-FDG exposure, and there was no evidence the P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
2
7
1
1
Order By: Relevance
“…In contrast to May et al other authors, who measured γ-H2AX fluorescence intensity in patients' lymphocytes both before and after [ 18 F]FDG application, reported that they did not find significant changes [18,19]. Schnarr et al observed a varied response among ten patients when measuring γ-H2AX fluorescence intensity by flow cytometry before and after [ 18 F]FDG PET scans [18]. Prasad et al also used flow cytometry to measure γ-H2AX fluorescence intensity in the lymphocytes of 25 patients and reported an increase in the signal after the PET/CT scan that was, however, not significant because of a high inter-individual variation [19].…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…In contrast to May et al other authors, who measured γ-H2AX fluorescence intensity in patients' lymphocytes both before and after [ 18 F]FDG application, reported that they did not find significant changes [18,19]. Schnarr et al observed a varied response among ten patients when measuring γ-H2AX fluorescence intensity by flow cytometry before and after [ 18 F]FDG PET scans [18]. Prasad et al also used flow cytometry to measure γ-H2AX fluorescence intensity in the lymphocytes of 25 patients and reported an increase in the signal after the PET/CT scan that was, however, not significant because of a high inter-individual variation [19].…”
Section: Discussioncontrasting
confidence: 66%
“…In contrast to May et al other authors, who measured γ-H2AX fluorescence intensity in patients' lymphocytes both before and after [ 18 F]FDG application, reported that they did not find significant changes [18,19]. Schnarr et al observed a varied response among ten patients when measuring γ-H2AX fluorescence intensity by flow cytometry before and after [ 18 F]FDG PET scans [18].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…B. bei der PRRT unterschritten wird. Systematische Daten zur patientenspezifischen Strahlenempfindlichkeit wurden bisher nur in wenigen Arbeiten beschrieben [6,23]. Es ist zu erwarten, dass die neueren Untersuchungen zur Dosisabhängigkeit und zum zeitlichen Verlauf der DNA-Reparatur in Leukozyten mittels des deutlich empfindlicheren γ-H2AX-Assays Information über die individuellen Reparaturfähigkeiten von Patienten liefern.…”
Section: Schlussfolgerungenunclassified
“…Related to hormesis is the adaptive response, where a low-dose stress can protect cells or whole organisms from a subsequent high-dose exposure. A variety of different stressors have been shown to induce an adaptive response by reducing damage from high-dose ionizing radiation, including lowdose radiation (6)(7)(8), thermal stress (9-11) and oxidative chemical compounds (12)(13)(14). Similar cellular and molecular mechanisms have been implicated in both the adaptive response and radiation hormesis (15).…”
Section: Introductionmentioning
confidence: 99%